2018
DOI: 10.1021/acs.est.7b06573
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Neonicotinoid Exposure for Bees in Rural and Peri-urban Areas of the U.K. during the Transition from Pre- to Post-moratorium

Abstract: Concerns regarding the impact of neonicotinoid exposure on bee populations recently led to an EU-wide moratorium on the use of certain neonicotinoids on flowering crops. Currently, evidence regarding the impact, if any, the moratorium has had on bees' exposure is limited. We sampled pollen and nectar from bumblebee colonies in rural and peri-urban habitats in three U.K. regions: Stirlingshire, Hertfordshire, and Sussex. Colonies were sampled over three years: prior to the ban (2013), during the initial impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The presence of pesticide residues in the foraging landscape also has the potential to affect colony growth in honeybees (Tsvetkov et al 2017;Woodcock et al 2017;although cf. Rundlöf et al 2015) and has been shown to be higher in rural than urban areas (Botías et al 2017;Nicholls et al 2018 although cf. Johnson and Pettis 2014).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of pesticide residues in the foraging landscape also has the potential to affect colony growth in honeybees (Tsvetkov et al 2017;Woodcock et al 2017;although cf. Rundlöf et al 2015) and has been shown to be higher in rural than urban areas (Botías et al 2017;Nicholls et al 2018 although cf. Johnson and Pettis 2014).…”
Section: Discussionmentioning
confidence: 97%
“…It is widely recognised that pollinators are declining, and that pesticides use in conventional farming is a contributing factor (Goulson et al 2015), yet the impact of pesticides in urban areas is much less well studied. Recent studies comparing exposure of bees in rural and urban areas of the UK have found bees in urban areas are indeed exposed to pesticides, often at comparable levels to bees in rural areas (Nicholls et al 2018). Awareness of potential risks to human and environmental health is key, as is disseminating information about alternative pest control methods, such as agro-ecological methods.…”
Section: Contributions To Sustainable Development Goal 15 (Life On Land)mentioning
confidence: 99%
“…Therefore, continued intensive use is likely to have severe consequences on insect species numbers, with knock-on effects for the ecosystem, aquatic life, birds and mammals in addition to potential toxicity to humans 11,[20][21][22] . Despite the recent European Union (EU) ban of three major neonicotinoids (the nitroimines: imidacloprid, clothianidin and thiamethoxam, the latter being a prodrug for clothiandin 23 ), neonicotinoids remain the most widely used class of insecticide globally, with a number of studies showing there has been no decrease in the quantity of banned neonicotinoids found in different populations of honey and bumble bee across Europe a year after the ban 24,25 . Furthermore, some national governments have granted multiple exemptions for the spraying of oil seed rape and a number of other applications 26 , and neonicotinoids have high solubility and persistence in the environment 11 .…”
Section: Introductionmentioning
confidence: 99%